2012
DOI: 10.1159/000342596
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Chamber Clotting during Continuous Renal Replacement Therapy: Vertical versus Horizontal Blood Flow Entry

Abstract: Background: The continuous renal replacement therapy (CRRT) bubble trap chamber is a frequent site of clotting. Aims: To assess clot formation when comparing our standard ‘vertical’ blood entry chamber (BEC) with a new ‘horizontal’ BEC. Methods: Adult ICU patients requiring CRRT were treated with the vertical BEC and then a similar subsequent cohort with the horizontal BEC in continuous veno-venous haemofiltration mode. Results: 40 chambers were assessed for each design. Circuit life was 13.9 ± 9.5 h for the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Two small studies showed no benefit from different sites of heparin delivery [ 55 , 56 ]. No benefit was observed using a modified horizontal bubble trap on the return line [ 57 ], priming the circuit with albumin before use [ 58 ] to improve biocompatibility or by the presence or absence of a fluid warmer on the return blood path [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two small studies showed no benefit from different sites of heparin delivery [ 55 , 56 ]. No benefit was observed using a modified horizontal bubble trap on the return line [ 57 ], priming the circuit with albumin before use [ 58 ] to improve biocompatibility or by the presence or absence of a fluid warmer on the return blood path [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The coagulation degree of plasma separator after treatment was divided into 4 classes [22,23]: Class I, 1-3 blood clots at the tip of the filter; Class II, annular blood clot at tip of filter; Class III, several large blood clots at the tip of the filter; and Class IV, completely coagulated on the lid. The degree of vein ampulla coagulation was divided into 5 classes [23]: Class I, no coagulation in vein ampulla after blood return; Class II, small clots in the filter at the bottom of vein ampulla; Class III, circular clots at the top of vein ampulla and clots at the bottom of the filter; Class IV, large clots on the upper and bottom of vein ampulla filter; and Class V, completely coagulation in the entire vein ampulla and requirement of replacement venous blood tube. Blood samples were collected from peripheral veins and arteries before and after treatment.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…The gas and blood interface, along with surface movement, causes cell smearing on the chamber walls. Adjustment of the blood level high in the chamber may reduce this by reducing blood splashing on the surface and coagulation [35,36].…”
Section: Filter Life With Your Crrt Usementioning
confidence: 99%